Kamus Sistem Isyarat Bahasa Indonesia (KASIBI) dengan Voice Recognition sebagai Pendukung Belajar Bahasa Isyarat Berbasis Android - Mohammad Zikky; Zulhaydar Fairozal Akbar; Setyabudi Utomo (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2019)
Deaf children are children who have disturbances in the sense of hearing, both permanent and non-permanent. Deaf children have obstacles in terms of communication, both communicating verbally and in writing, exacerbated by the difficulty of getting exclusive learning media for deaf children also complicates parents to be able to assist in the learning process of deaf children. Therefore, there is needs an exclusive learning media dictionary for deaf children, so it can help parents in helping the learning process of them. Based on these problems, this research proposes an application